Pengaruh Interaksi dan Nilai Interaksi pada Percobaan Faktorial (Review) - TENAYA, I MADE NARKA (Agrotrop : Journal on Agriculture Science; Vol 5 No 1 (2015))
The Effect of Interaction and Value of Interaction on Factorial Experiment. In a factorial experiment, the effect of combination treatment can be divided into three components: (1) a simple effect; (2) the influence of factors, and (3) the influence of interactions. Interaction Value (NI) contained in the combination treatment is different with the influence of interaction, and the interaction value (NI) is always found in combination treatment, which may have a positive, zero, and negative value, under the condition that the sum of interaction value (NI) at ech level of treatment equals to zero. The formula of value of interaction (NI): NI ij = Yij - Yi. - Y.j + Y..
Keywords: effect of combination, simple effect, main effect, influence of interaction, interaction value (NI)